Ultrafine SiOx/C nanospheres and their pomegranate-like assemblies for high-performance lithium storage. Issue 30 (18th July 2018) - Yu, Qiang; Ge, Peipei; Liu, Zhenhui; Xu, Ming; Yang, Wei; Zhou, Liang; Zhao, Dongyuan; Mai, Liqiang
Abstract : Pomegranate-like SiO x /C microspheres demonstrate high specific capacity and outstanding cyclability (1024 mA h g −1 after 200 cycles) for lithium storage. Abstract : The application of silicon oxide (SiO x )-based anode materials in lithium-ion batteries is hampered by their low conductivity and large volume expansion. To tackle both issues, ultrafine SiO x /C composite nanospheres with a uniform diameter of ∼40 nm were fabricated through a tri-component co-assembly approach. The ultrafine SiO x /C nanospheres demonstrated a high specific capacity of 895 mA h g −1 after 200 cycles at 200 mA g −1 . At a high current density of 1 A g −1, a capacity of 828 mA h g −1 could be achieved after 1000 cycles. The ultrafine SiO x /C nanospheres were further assembled into pomegranate-like assemblies through spray drying. The resultant pomegranate-like structure manifested a discharge capacity of 1024 mA h g −1 after 200 cycles at 500 mA g −1 .